Environmental and Related Social Costs of the Tax Treatment of Company Cars and Commuting Expenses - Roy, Rana (OECD Environment Working Papers, 2014)
This paper builds upon a recent OECD paper on the personal tax treatment of company cars and commuting expenses in OECD member-countries and aims to arrive at a better understanding of the environmental and related social costs of the tax treatment described therein. The paper begins with an analysis of the larger transport market, which is the primary storehouse of evidence on the nature and extent of the environmental impacts of the various transport modes, the relative importance of the proximate and underlying determinants of these impacts, and the elasticities and functional relationships at work. Non-linearities in the relevant elasticities and functional relationships mean that the tax treatment of company cars may have a greater or lesser impact than is suggested by the size of the company car market.